2014
DOI: 10.1073/pnas.1406324111
|View full text |Cite
|
Sign up to set email alerts
|

Economic demand predicts addiction-like behavior and therapeutic efficacy of oxytocin in the rat

Abstract: Development of new treatments for drug addiction will depend on high-throughput screening in animal models. However, an addiction biomarker fit for rapid testing, and useful in both humans and animals, is not currently available. Economic models are promising candidates. They offer a structured quantitative approach to modeling behavior that is mathematically identical across species, and accruing evidence indicates economic-based descriptors of human behavior may be particularly useful biomarkers of addiction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
211
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(238 citation statements)
references
References 50 publications
(87 reference statements)
24
211
3
Order By: Relevance
“…However, a previous report in rats indicated that there was not an association between demand for sucrose and DD of a sucrose reward (Koffarnus and Woods, 2013). Given that demand is often interpreted as a measure of motivation (Amlung et al, 2012; Bentzley et al, 2014; Zimmer et al, 2012), differences in sucrose motivation between rat lines are unlikely to account for the relatively higher DD in P rats reported here.…”
Section: Discussionmentioning
confidence: 76%
“…However, a previous report in rats indicated that there was not an association between demand for sucrose and DD of a sucrose reward (Koffarnus and Woods, 2013). Given that demand is often interpreted as a measure of motivation (Amlung et al, 2012; Bentzley et al, 2014; Zimmer et al, 2012), differences in sucrose motivation between rat lines are unlikely to account for the relatively higher DD in P rats reported here.…”
Section: Discussionmentioning
confidence: 76%
“…10A; España et al, 2010; Oleson et al, 2011)). Once stable responding under the threshold schedule was achieved, data were fitted to an exponential demand curve to determine Q 0 , a measure of consumption at null cost, and P max , the behavioral economic index of price (Bentzley et al, 2014; Oleson et al, 2011). Under this schedule, Q 0 represents the animal’s preferred level of cocaine consumption while P max represents motivation to maintain preferred blood levels of cocaine.…”
Section: 0 Resultsmentioning
confidence: 99%
“…In these studies we showed that susceptible subjects display increased motivation ( P max ) to obtain cocaine, with a corresponding decrease in consumption at null cost ( Q 0 ). This is a particularly interesting observation as motivation to obtain cocaine under the threshold schedule has recently been shown to positively correlate with several other features of an addiction-like phenotype including: (i) resistance to instrumental extinction, (ii) cue- and cocaine-induced reinstatement, and (iii) persistence of drug taking in the face of punishments (Bentzley et al, 2014). Furthermore, low initial levels of cocaine consumption were found to predict a heightened propensity to escalate cocaine taking (Bentzley et al, 2014).…”
Section: 0 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the current study provides a strong starting point for understanding the role of orexin/hypocretin in pathological drug seeking but at the same time highlights a number of key questions that must be addressed by future studies. For example, the authors have elegantly implicated the orexin/hypocretin system as a key modulator of escalation of drug intake, but it remains to be demonstrated whether this mechanism is also involved in the regulation of other key addiction behaviors known to be enhanced by LgA such as compulsive (punished) responding and economic demand (8). Given the persistent nature of addiction, it is also important that future studies seek to determine whether the electrophysiological changes observed here immediately following cocaine self-administration persist into withdrawal and to what extent they contribute to relapse-like behavior.…”
mentioning
confidence: 99%